Study of the Relationship between Radiocarbon Dating (¹⁴C Isotope) and Dendrochronology: Applications of Nuclear Physics in Archaeology - Sari, Insira Nayla; Putri, A. Surtika; Lidasti, Atiqah; W, Theresia Lasri Da Costa; Yulia, Reski; Nurhayati, Nurhayati; Resky Irfanita (Physics Department, Faculty of Mathematics and Natural Sciences, Universitas Negeri Makassar, 2025)
This article presents the results of an in-depth literature review on radiocarbon dating, tracing its development from the earliest stages. Particular emphasis is placed on the role of carbon-14 (¹⁴C) in determining the age of materials and on how dendrochronological calibration can enhance accuracy. The discussion also focuses on the decay of carbon-14 isotopes and their half-life, the methods and principles underlying radiocarbon dating, dendrochronological calibration, and other applications of radiocarbon dating in age determination. In conclusion, the article highlights the significant contributions of radiocarbon dating and dendrochronology in addressing critical challenges in archaeological research, thereby enabling scholars to gain a deeper understanding of natural history and human culture.